Persepsi Sosial/Masyarakat Terhadap Anak Berkebutuhan Khusus Secara Fisik - Rahel Putriani; Ghea Clara Salsabila; Rachmad Aldi; Opi Andriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Community Perceptions of Children with Special Physical Needs in Central Rimbo District, Muara Bungo Regency. This research aims to determine the perception of the community in Muara Bungo Regency regarding children with special needs and to determine the support of the community in Rimbo Tengah District, Muara Bungo Regency for children with special physical needs. This research uses a type of qualitative research which is analyzed descriptively. Data collection techniques were obtained using field research through observation, interviews and documentation methods, involving several community leaders. The results of this research show that regarding the perception of the community in Central Rimbo District, Muara Bungo Regency towards children with special needs, no human being is born perfect, because Allah SWT created humans equipped with their respective strengths and weaknesses. Likewise, for people who have physical limitations, children with special needs are stated in the cultural norms and values as well as community support in Central Rimbo District, Muara Bungo Regency for children with special needs. Community sympathy, especially the community in Central Rimbo District, Muara Bungo Regency, always provides support or support for children with special needs. One way of showing this support is social support as the presence of people who personally provide advice, motivate, direct, encourage and show a way out when experiencing problems and when experiencing obstacles in carrying out activities in a directed manner to achieve goals.